Hypophosphatemia predicts a failure to recover from adefovir‐related renal injury after dose reduction in lamivudine‐resistant hepatitis B patients. Issue 12 (3rd February 2017) - Yamamoto, Tatsuo; Maruyama, Yasuhiko; Ohashi, Naro; Yasuda, Hideo; Shinozaki, Masami
Abstract : Aim: In chronic hepatitis B patients receiving 10 mg adefovir, dose reduction is recommended when renal injury appears. However, recovery is not always achieved and markers that recommend switching to another antiviral agent are unknown. We investigated adefovir‐related renal injury, recovery after dose reduction, and their predictors. Methods: The renal injury in 77 chronic hepatitis B patients receiving 10 mg adefovir and recovery after dose reduction to alternate day administration in those with adefovir‐related renal injury were assessed. The predictors for >20% estimated glomerular filtration rate (eGFR) decline following treatment with 10 mg adefovir and for >20% eGFR recovery after dose reduction were investigated. Results: The adefovir dose was reduced in 26 patients (34%) at 59 ± 30 (mean ± standard deviation) months of 10 mg adefovir treatment because of decreases in eGFR (cumulative incidence 27%), serum phosphorus (9%), and uric acid (16%) levels, and increases in alkaline phosphatase (20%), bone type alkaline phosphatase (18%), urinary α1‐microglobulin (18%), and urinary N‐acetyl‐β‐D‐glucosaminidase (18%) levels. The only significant predictor for >20% eGFR decline was age ≥50 years at the start of 10 mg adefovir treatment. The cumulative eGFR recovery rate was 42% at 42 ± 27 months after dose reduction, and ≥2.5 mg/dL serum phosphorus level at dose reduction was the only significant predictor for >20% eGFR recovery after dose reduction. Conclusion: Patients aged ≥50 years are predisposed to adefovir‐related renal injury and switching to another antiviral agent rather than adefovir dose reduction is recommended when hypophosphatemia is observed.